Blocking serine protease activity prevents semenogelin degradation leading to hyperviscous semen in humans. Issue 5 (29th January 2022) - Anamthathmakula, Prashanth; Erickson, Jeffery A; Winuthayanon, Wipawee
Abstract: Prostate-specific antigen (PSA) is a prostate-specific serine protease enzyme that hydrolyzes gel-forming proteins (semenogelins) and changes the semen from gel-like to watery viscosity, a process called semen liquefaction. Highly viscous semen and abnormal liquefaction reduce sperm motility and contribute to infertility. Previously, we showed that nonspecific serine protease inhibitor (AEBSF) prevented proteolytic degradation of semenogelin in mice. However, it is unclear whether similar effect could be recapitulated in fresh human ejaculates. Therefore, in this study we evaluated the effect of AEBSF on the degradation of semenogelin (SEMG1) and its subsequent impact on semen liquefaction and sperm motility in fresh semen ejaculates collected from healthy men. We found that AEBSF showed a dual contraceptive action where it effectively 1) prevented degradation of SEMG1 resulting in viscous semen and 2) decreased sperm motility in human semen samples. However, the impact of AEBSF on sperm motility and viability could be due to its inhibitory activity toward other serine proteases or simply due to its toxicity. Therefore, to determine whether inhibition of PSA activity alone could disrupt SEMG1 degradation and contribute to hyperviscous semen, a neutralizing PSA antibody was used. We found that PSA antibody effectively prevented SEMG1 degradation with a subtle impact on sperm motility. These findings suggest that the target inhibition of PSA activity can prevent proteolytic degradation of SEMG1 and block liquefaction process, resulting in hyperviscous semen. As it is currently unknown if blocking semen liquefaction alone could prevent pregnancy, it needs further extensive studies before drawing any translational conclusions. Graphical abstract: